Numerical Fiscal Rules for Economic Unions : the Role of Sovereign Spreads - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper ;, 2021)
We study gains from introducing a common numerical fiscal rule in a "Union" of model economies facing sovereign default risk. We show that among economies in the Union, there is significant disagreement about the common debt limit the Union should implement: the limit preferred by some economies can generate welfare losses in other economies. In contrast, a common sovereign spread limit results in higher welfare across economies in the Union.